Makna dan Nilai Pertunjukan Wayang Golek Menak Kebumen Lakon Wrahatkustur Ngraman Sajian Sunarto Sindhu - Bagong Pujiono (Institut Seni Indonesia Surakarta, 2019)
This study reveals the values and meanings implied in Wayang Golek Kebumen Lakon Wrahatkustur Ngraman by Sunarto Sindu. Lakon Wrahatkustur Ngraman tells about moral teachings for every human in relation to the God and social interaction. Javanese culture as the root of norms for Javanese people is used to be a reference to reveal the values reflected in the Lakon. The method used in data collection includes observation of material objects, interviews with competent interviewees, and literary studies. The results show that the performance of wayang golek Kebumen Wrahatkustur Ngraman reflects the values of community life that are closely related to the Javanese culture. Those values are reflected in Catur especially in the presented Gunem. The characters presented in Lakon have their own roles in delivering messages to the audience. Keywords: values, meanings, Wayang Golek Kebumen, Wrahatkustur Ngraman